Plan de seguridad y salud ocupacional para la Empresa Pollos Gusy Matriz, de la ciudad de Loja - Gonzáles Yaguachi, Edy Yasmani (2020)
This thesis called "Occupational Safety and Health Plan for the Pollos Gusy Matriz Company, in the City of Loja", whose general objective was: To prepare an Occupational Safety and Health Plan for the Pollos Gusy Matriz company, in the city of Loja and our specific objectives were: to make a diagnosis of the current situation and prepare an occupational health and safety plan. The methods used for the development of the investigation were deductive that were identified to identify the regulations that the company complies with or not; the analytic that served to analyze the information collected; and the description that required detailing the current situation. To obtain information, an interview was conducted with the administrator, a survey of the 12 workers and an observation guide based on the checklist of compliance with legal regulations on safety and health at work.As results, it was found that: The restaurant does not have an Internal Hygiene and Safety regulation, the delegate of occupational health and safety has not been selected, 58.33% of workers to incidents or accidents during their working day, 91.67% of the personnel have been given personal protective equipment, 66.67% stated that they handle chemical substances, 83.33% of the personnel have not received training in first aid, 58, 33% do not know the Correct use of the extinguisher, the electrical system is malfunctioning, no necessary measures have been taken to mitigate the effects of forced positions and repetitive movements, medical examinations are not carried out on workers, they lack an immunization program and the First aid kit does not have the necessary tools to cover an emergency. The collected information served to elaborate an Occupational Health and Safety Plan where possible solutions to the problems encountered are proposed and our main objective is to serve as a guide in occupational health and safety, to obtain optimal work solutions and comply with the requirements legal requirements of the Ecuadorian government.